Release of Bioactive Molecules Using Metal Complexes - Simpson, Peter; Schatzschneider, U. (2014)
The biological activity of molecules is modulated by coordination to a transition metal centre. Ideally, this results in a completely inactive system, which acts as a prodrug, from which the bioactive component can be released by a specific trigger mechanism in a spatially and temporally controlled way. This chapter focuses on three different applications, to highlight general concepts as well as current challenges in the area: (1) the release of small-molecule messengers such as nitric oxide (NO) and carbon monoxide (CO) from the metal coordination sphere; (2) the "photouncaging" of organic neurotransmitters from metal complexes; and (3) the hypoxia-activated release of anticancer-active compounds from metal-based prodrugs.